Nunca llueve en Timber Creek - Lewis, Ali, 1976- (Tres edades, 2015)
Danny Dawson lives in the middle of the Australian outback. His older brother Jonny was killed in an accident last year but no-one ever talks about it. And now it's time for the annual muster. The biggest event of the year on the cattle station, and a time to sort the men from the boys. But this year things will be different: because Jonny's gone and Danny's determined to prove he can fill his brother's shoes; because their fourteen-year-old sister is pregnant; because it's getting hotter and hotter and the rains won't come; and, because cracks are beginning to show ... When Danny's mum admits she can't cope, the family hires a housegirl to help out - a wide-eyed English backpacker. She doesn't have a clue what she's let herself in for. And neither do they.